The impact of CFNS-causing EFNB1 mutations on ephrin-B1 function - Wieacker Peter; Tasic Velibor; Gucev Zoran; Steiner Bernhard; Makarov Roman; Wieland Ilse (BMC, 2010)
Abstract Background Mutations of EFNB1 cause the X-linked malformation syndrome craniofrontonasal syndrome (CFNS). CFNS is characterized by an unusual phenotypic pattern of inheritance, because it affects heterozygous females more severely than hemizygous males. This sex-dependent inheritance has been explained by random X-inactivation in heterozygous females and the consequences of cellular interference of wild type and mutant EFNB1-expressing cell populations. EFNB1 encodes the transmembrane protein ephrin-B1, that forms bi-directional signalling complexes with Eph receptor tyrosine kinases expressed on complementary cells. Here, we studied the effects of patient-derived EFNB1 mutations predicted to give rise to truncated ephrin-B1 protein or to disturb Eph/ephrin-B1 reverse ephrin-B1 signalling. Five mutations are investigated in this work: nonsense mutation c.196C > T/p.R66X, frameshift mutation c.614_615delCT, splice-site mutation c.406 + 2T > C and two missense mutations p.P54L and p.T111I. Both missense mutations are located in the extracellular ephrin domain involved in Eph-ephrin-B1 recognition and higher order complex formation. Methods Nonsense mutation c.196C > T/p.R66X, frameshift mutation c.614_615delCT and splice-site mutation c.406+2T > C were detected in the primary patient fibroblasts by direct sequencing of the DNA and were further analysed by RT-PCR and Western blot analyses. The impact of missense mutations p.P54L and p.T111I on cell behaviour and reverse ephrin-B1 cell signalling was analysed in a cell culture model using NIH 3T3 fibroblasts. These cells were transfected with the constructs generated by in vitro site-directed mutagenesis. Investigation of missense mutations was performed using the Western blot analysis and time-lapse microscopy. Results and Discussion Nonsense mutation c.196C > T/p.R66X and frameshift mutation c.614_615delCT escape nonsense-mediated RNA decay (NMD), splice-site mutation c.406+2T > C results in either retention of intron 2 or activation of a cryptic splice site in exon 2. However, c.614_615delCT and c.406+2T > C mutations were found to be not compatible with production of a soluble ephrin-B1 protein. Protein expression of the p.R66X mutation was predicted unlikely but has not been investigated. Ectopic expression of p.P54L ephrin-B1 resists Eph-receptor mediated cell cluster formation in tissue culture and intracellular ephrin-B1 Tyr324 and Tyr329 phosphorylation. Cells expressing p.T111I protein show similar responses as wild type expressing cells, however, phosphorylation of Tyr324 and Tyr329 is reduced. Conclusions Pathogenic mechanisms in CFNS manifestation include impaired ephrin-B1 signalling combined with cellular interference.